Safety Culture in European Commercial Aviation Industry: A Review - Bekesius, Vilmantas (2017)
Ever since the introduction of the “Safety Culture” concept in INSAG’s report following the 1986 Chernobyl nuclear disaster, it quickly became a subject of interest among numerous academics. It rapidly gained popularity within numerous industries, with a primary focus on high-reliability organizations and high-risk industries. The aviation industry was one of the first pioneers, which have quickly adopted this concept into the core of their business model, as a widespread impact arising from the safety issues in aviation industry was recognized to be highly severe. A high number of previous researchers have addressed the concept of safety culture within a number of diverse industries, including banking, finance, and healthcare. However, a safety culture assessment based on information available from annual reports has never been performed in the past. Therefore, this paper explores the Safety Culture in European Commercial Aviation industry based on annual reports of 5 largest European airlines in the period from 2014 to 2016. A content analysis will be carried out using the NVivo11 to analyse the annual reports, and the acquired data will be examined for better assessment of the Safety Culture in European aviation industry.